Theoretical and experimental analyses of dynamic deformation in low-frequency vibration-assisted drilling of CFRP/Ti stacks. (October 2022) - Yan, Chaoren; Qian, Ning; Chen, Yan; Wang, Yongqing; Guo, Nan; Lin, Hai
Abstract: Hole-making of stacks composed of carbon-fiber-reinforced plastic (CFRP) and titanium alloy under Low-frequency vibration-assisted drilling (LFVAD) is beneficial to both machining quality and tool wear. However, complicated deformation of the bottom Ti layer and even severe interfacial damage appears under the thrust forces with periodic fluctuations. Owing to lack of theoretical guidance in suppressing the deformation, this study established an analytical model to explain the influence of the fluctuating thrust force on the deformation of the workpiece. Data from validation trials performed on the CFRP/Ti stacks show that the deformation and thrust forces exhibit the same fluctuation behavior. The prediction errors of the average value and vibration amplitude of the Ti deformation were within 0.9 % and 10.7 %, respectively. Finally, a case study was conducted to optimize the drilling parameters in LFVAD of CFRP/Ti stacks based on the proposed model. As a result, the CFRP delamination damage was reduced by 17.0 %, and the stack drilling efficiency increased by 40.8 %. Highlights: The effect of drilling parameter and workpiece structure on the deformation of workpiece under LFVAD process is explained； The influence of the fluctuating thrust force on the deformation of the workpiece are discussed and analyzed； A preferable result for optimizing the machining parameters is obtained in LFVAD of CFRP/Ti stacks.